Bacteriological Profile of Neonatal Sepsis: A Hospital Based Study - Shrestha, NJ; Subedi, KU; Rai, GK (Journal of Nepal Paediatric Society, 2011)
Introduction: Neonatal sepsis is a major cause of mortality and morbidity in newborn. There are many factors that contribute to neonatal sepsis. The organisms responsible for early onset and late onset sepsis are different. Objective: This study was conducted to analyze the organisms responsible for early onset and late onset neonatal sepsis. Materials and Methods: A prospective hospital based study over the period of one year was conducted at neonatal intermediate care unit of Kanti Children's Hospital, Maharajgunj, Kathmandu, Nepal. Results: Organisms were isolated in 6.1% of the collected blood samples. The male female ratio of culture proven sepsis was 1.9:1. Escherichia coli were found to be the most common organism in both early onset and late onset sepsis. Staphylococcus aureus was more common in late onset sepsis than early onset sepsis. Conclusion: Escherichia coli were the most common organism in both early onset and late onset sepsis. Staphylococcal aureus was significantly more common in late onset sepsis than early onset sepsis. Key words: Bacteriological profile; early onset sepsis; late onset sepsis; neonate DOI: 10.3126/jnps.v31i1.4158 J Nep Paedtr Soc 2010;31(1):1-5